Preparation method and application of composite functional material of ball-milled micron zero-valent iron doped phosphate and biochar

By ball milling a composite material of micron zero-valent iron with phosphate and biochar, the problem of easy agglomeration and oxidation of mZVI is solved, significantly improving the fixation capacity of heavy metals, and achieving efficient fixation of Pb(II) and Cd(II) in water and soil.

CN119735279APending Publication Date: 2025-04-01HAINAN UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411924874.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing micron zero-valent iron (mZVI) has low pollutant removal efficiency in soil and water, is prone to agglomeration and oxidation, resulting in reduced surface area and reduced reactivity.

Method used

By ball milling micron zero-valent iron composites with phosphate and biochar, prevent agglomeration and oxidation, and increase surface charge and adsorption sites.

Benefits of technology

The composite material has significantly improved the fixation ability of heavy metal ions, and achieved efficient fixation of Pb(II) and Cd(II) in water and soil, with long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735279A_ABST
    Figure CN119735279A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite functional material of ball-milled micron zero-valent iron doped phosphate and biochar, and relates to the technical field of micron zero-valent iron preparation. According to the invention, a composite functional material of ball-milled micron zero-valent iron doped phosphate and biochar is prepared by ball-milling zero-valent iron, phosphate and biochar, the banana peel biochar and KH2PO4 are selected to synthesize an mZVI composite material, the introduction of biochar and KH2PO4 increases the surface charge of mZVI, more active sites are provided for adsorption of heavy metals, and the adsorption efficiency of heavy metals is improved. Therefore, the problem of agglomeration of the mZVI is prevented. The preparation method and the application of the composite functional material of the ball-milled micron zero-valent iron doped phosphate and biochar can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of micron zero-valent iron, and in particular to a preparation method and application of a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar. Background Art

[0002] With the continuous development of society and the continuous progress of industry, human activities have greatly enhanced the release of heavy metals and related compounds, leading to widespread pollution of soil and water bodies. In the past few decades, lead and cadmium have mainly contaminated 19.4% of agricultural soils in China. The relevant survey report in 2014 showed that the points where inorganic pollutants exceeded the standard in my country accounted for 82.8% of the total pollution points, among which the points where inorganic pollutants such as cadmium, lead, arsenic and chromium exceeded the standard were 7.0%, 1.5%, 2.7% and 1.1% respectively. Pb(II) has adverse effects on the immune, cardiovascular, respiratory, reproductive and nervous systems due to its bioaccumulation and non-degradability, posing a major health risk. Cd(II) has harmful effects on the cardiovascular system, bones, kidneys, stomach and reproductive functions due to its toxicity, which is detrimental to human health. The mobility, toxicity and persistence of Pb(II) and Cd(II) enable them to accumulate rapidly in the environment, causing long-term damage to human health and ecosystems. Therefore, the problem of co-pollution of Pb(II) and Cd(II) in the environment is imminent.

[0003] At present, bioremediation, physical remediation and chemical remediation are commonly used in contaminated soil. Among them, in-situ chemical passivation technology has a significant effect on heavy metal immobilization due to its high efficiency, easy application and cost-effectiveness. A variety of modified materials, such as micron zero-valent iron (mZVI), biochar, lime, zeolite and clay, have successfully achieved the stabilization of heavy metals in contaminated soil. mZVI has a strong reduction capacity and a large surface area, which enables it to effectively adsorb and fix Pb(II) and Cd(II) heavy metal ions. However, mZVI has two major defects: easy agglomeration and easy oxidation. Agglomeration will reduce the effective specific surface area, thereby reducing the removal efficiency of mZVI from soil and water. Easy oxidation is another problem in the application of mZVI, because its tiny particle size and wide external area make it exposed to the air, and it is easy to oxidize rapidly in air or water to form less active iron oxides or hydroxides.

[0004] In order to deal with the agglomeration problem, strategies such as synthesizing mZVI composites using materials such as biochar have been developed to prevent agglomeration. In addition, phosphates can not only prevent particle aggregation, but also increase the surface charge of biochar and mZVI, providing more adsorption sites for both, and improving the overall stability. In order to prevent mZVI from being oxidized, ball milling mZVI with materials such as biochar can be used to reduce premature oxidation of the material. However, the selection of different biomass raw materials and phosphorus sources, as well as the preparation steps and pyrolysis conditions have a huge impact on the properties of the materials, so it is very important to optimize the parameters related to material preparation. Although mZVI, phosphates and biochar have been used individually as effective stabilizers for heavy metals such as lead and cadmium, their combined use as composite materials has not been widely explored.

[0005] In view of the above problems, it is urgent to find a modification method that is simple in preparation and can solve the above-mentioned defects of mZVI, and then apply it to the long-term fixation of heavy metals in soil. Summary of the invention

[0006] The purpose of the present invention is to solve the above technical problems and to provide a preparation method and application of a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar.

[0007] A method for preparing a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar is carried out according to the following steps:

[0008] Step S1: preparing biochar;

[0009] The pretreated banana peel powder is placed in a tube furnace, heated to 400-600° C. in a nitrogen atmosphere, and pyrolyzed at 400-600° C. for 110-130 minutes; after the pyrolysis, the banana peel powder is soaked in a hydrochloric acid solution, and then rinsed and dehydrated to obtain biochar;

[0010] Step S2: preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar;

[0011] The biochar obtained in step S1 is placed in a ball mill with micron zero-valent iron and KH2PO4, wherein the grinding balls in the ball mill are composed of large balls, medium balls and small balls, and the number ratio of the large balls, medium balls and small balls is (1-3): (15-17): (14-16); the ball mill is placed in a planetary ball mill, and after ball milling for 6-18 hours, it is sieved through a 100-mesh sieve to obtain a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar.

[0012] An application of a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar, and an application of the composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar in removing chromium from water and soil.

[0013] Beneficial effects of the present invention:

[0014] (1) The present invention prepares a composite functional material (P-mZVIBC) of ball-milled micronized zero-valent iron doped with phosphate and biochar by ball-milling zero-valent iron, phosphate and biochar. 500 ), by selecting banana peel biochar and KH2PO4 to synthesize mZVI composite materials, the introduction of biochar and KH2PO4 increases the surface charge of mZVI, providing more active sites for the adsorption of heavy metals, thereby preventing the problem of mZVI agglomeration; the introduction of KH2PO4 will form a layer of iron-phosphorus compounds on the surface of mZVI, preventing the formation of iron oxides on the surface of mZVI and thus reducing its reaction activity. At the same time, the physical ball milling method can not only prevent the agglomeration and oxidation of mZVI, but also enhance the distribution of phosphate and biochar on the surface of mZVI during the ball milling process. The hydroxyl, carbonyl and carboxyl groups of banana peel biochar improve its binding ability with iron and phosphate groups, thereby significantly improving the composite material's ability to fix heavy metal ions.

[0015] (2) The present invention provides a heavy metal remediation agent that can be applied to both water and soil, P-mZVIBC 500 It has a wide adaptability to pH and has little effect on the fixation of Pb(II) and Cd(II) in the range of 25-45°C. Compared with other remediation agents, it can fix Pb(II) and Cd(II) in the soil within 20 days, maintain long-term stability, and achieve efficient fixation of heavy metals Pb(II) and Cd(II) in water and soil, promoting the development and application of heavy metal remediation agents in water and soil.

[0016] The present invention can obtain a preparation method and application of a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The adsorption performance diagram of different repairing agents in Examples 1-4 is shown, the left column shows the equilibrium adsorption amount of Pb(II) by different materials, and the right column shows the equilibrium adsorption amount of Cd(II) by different materials;

[0018] Figure 2 Indicates P-mZVIBC in Example 1 500 SEM images of

[0019] Figure 3 Indicates P-mZVIBC in Example 1 500 and infrared spectra of P-mZVI;

[0020] Figure 4 Indicates P-mZVIBC in Example 1500 and X-ray diffraction patterns of P-mZVI;

[0021] Figure 5 Indicates P-mZVIBC in Example 1 500 The removal effect of Pb(II) and Cd(II) at different pH values. The upper curve represents the removal effect of Pb(II), and the lower curve represents the removal effect of Cd(II).

[0022] Figure 6 Indicates P-mZVIBC in Example 1 500 The removal effect of Pb(II) and Cd(II) at different times. The upper curve represents the removal effect of Pb(II), and the lower curve represents the removal effect of Cd(II);

[0023] Figure 7 Indicates P-mZVIBC in Example 1 500 The removal effect of Pb(II) at different temperatures, the curves from top to bottom represent 45℃, 35℃ and 25℃;

[0024] Figure 8 Indicates P-mZVIBC in Example 1 500 The removal effect of Cd(II) at different temperatures, the curves from top to bottom represent 45℃, 35℃ and 25℃;

[0025] Fig. 9 The figure shows the remediation effect of different remediation agents on Pb(II) and Cd(II) in soil in Example 1. The left column represents the equilibrium adsorption amount of Pb(II) by different materials, and the right column represents the equilibrium adsorption amount of Cd(II) by different materials. DETAILED DESCRIPTION

[0026] Specific implementation method 1: This implementation method is a method for preparing a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar, which is carried out according to the following steps:

[0027] Step S1: preparing biochar;

[0028] The pretreated banana peel powder is placed in a tube furnace, heated to 400-600° C. in a nitrogen atmosphere, and pyrolyzed at 400-600° C. for 110-130 minutes; after the pyrolysis, the banana peel powder is soaked in a hydrochloric acid solution, and then rinsed and dehydrated to obtain biochar;

[0029] Step S2: preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar;

[0030] The biochar obtained in step S1 is placed in a ball mill with micron zero-valent iron and KH2PO4, wherein the grinding balls in the ball mill are composed of large balls, medium balls and small balls, and the number ratio of the large balls, medium balls and small balls is (1-3): (15-17): (14-16); the ball mill is placed in a planetary ball mill, and after ball milling for 6-18 hours, it is sieved through a 100-mesh sieve to obtain a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar.

[0031] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the pretreated banana peel powder described in step S1 is processed according to the following steps: the banana peel is rinsed with distilled water and dried in an oven at 70-90°C for 12-36 hours; after drying, the banana peel is ground and then sieved with a 100-mesh sifter to obtain banana peel powder with a particle size of 0.13-0.17 mm.

[0032] The other steps are the same as those in the first specific implementation.

[0033] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that the nitrogen introduction rate in step S1 is 140-160 mL / min.

[0034] The other steps are the same as those in the first or second embodiment.

[0035] Specific implementation method 4: The difference between this implementation method and specific implementation methods 1 to 3 is that in step S1, the temperature is increased to 400-600°C at a heating rate of 5-10°C / min.

[0036] The other steps are the same as those in Specific Embodiments 1 to 3.

[0037] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that in step S1, the banana peel powder is placed in a 0.05-0.15M hydrochloric acid solution and soaked for 10-12 hours.

[0038] The other steps are the same as those in Specific Embodiments 1 to 4.

[0039] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that dehydration is performed at 70-90° C. in step S1.

[0040] The other steps are the same as those in Specific Embodiments 1 to 5.

[0041] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that the rotation speed of the ball mill in step S2 is 200-400 rpm.

[0042] The other steps are the same as those in Specific Embodiments 1 to 6.

[0043] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that the rotation direction of the ball milling process in step S2 is reversed every 2 to 4 hours.

[0044] The other steps are the same as those in Specific Embodiments 1 to 7.

[0045] Specific embodiment nine: The difference between this embodiment and any one of specific embodiments one to eight is that the mass ratio of the biochar, micron zero-valent iron and KH2PO4 described in step S2 is (0.1-0.2): (0.4-0.6): (0.7-0.8).

[0046] The other steps are the same as those in Specific Embodiments 1 to 8.

[0047] Specific embodiment ten: This embodiment is an application of a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar, and the application of the composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar in removing chromium from water and soil.

[0048] The following examples are used to verify the beneficial effects of the present invention:

[0049] Example 1: A method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar, comprising the following steps:

[0050] Step S1: preparing biochar;

[0051] 10g of banana peel was rinsed with distilled water twice and dried in an oven at 80°C for 24h; after drying, the banana peel was ground and sieved with a 100-mesh sieve to obtain banana peel powder with a particle size of 0.15mm; the pretreated banana peel powder was placed in a tube furnace, gradually heated from ambient temperature to 500°C at a heating rate of 10°C / min under a nitrogen flow of 150mL / min, and pyrolyzed at 500°C for 120min; after pyrolysis, the banana peel powder was soaked in a 0.1M hydrochloric acid solution for 12h to remove residual ash; then it was thoroughly rinsed with distilled water and dehydrated at 80°C to obtain biochar;

[0052] Step S2: preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar;

[0053] Put 0.15g of biochar obtained in step S1, 0.5g of micron zero-valent iron and 0.73g of KH2PO4 into a ball mill, wherein the grinding balls in the ball mill are composed of large balls, medium balls and small balls, and the number ratio of the large balls, medium balls and small balls is 2:16:15; put the ball mill into a planetary ball mill, and ball mill at an orbital speed of 300rpm for 12h, and the rotation direction of the ball milling process is reversed every 3h; finally, pass through a 100-mesh sieve to obtain a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar.

[0054] Example 2: In this example, a composite functional material of non-ball-milled micronized zero-valent iron doped with phosphate and biochar was prepared. Other experimental conditions were the same as those in Example 1.

[0055] Example 3: In this example, biochar was not added during the ball milling process. Other experimental conditions were the same as those in Example 1.

[0056] Example 4: In this example, phosphate and biochar were not added during the ball milling process. Other experimental conditions were the same as those in Example 1.

[0057] The composite functional material (P-mZVIBC) of ball-milled micronized zero-valent iron doped with phosphate and biochar prepared in the above embodiment 500 ), non-ball-milled micronized zero-valent iron doped with phosphate and biochar composite functional materials (*P-mZVIBC 500 ), ball-milled micron zero-valent iron doped phosphate composite functional materials (P-mZVI) and ball-milled micron zero-valent iron functional materials (mZVI) were respectively subjected to material ratio optimization experiments, water Pb (II) and Cd (II) removal experiments, and soil Pb (II) and Cd (II) pollution remediation experiments. The specific conclusions are as follows:

[0058] 1. Material selection:

[0059] The adsorption process is as follows: 0.05 ± 0.005 g of different repair agents P-mZVIBC are weighed using a balance 500 、*P-mZVIBC 500 , P-mZVI and mZVI, and added them into 150 mL conical flasks respectively. Then, 100 mL of 100 mg / L Pb(II) and Cd(II) solutions were added into the conical flasks. After shaking at 200 rpm for 4 h at 25 °C, the concentrations of Pb(II) and Cd(II) in the solutions were measured, and the removal rate of the adsorbent materials was calculated.

[0060] Figure 1 The adsorption performance diagram of different repair agents in Examples 1-4 is shown. The left column (black) represents the equilibrium adsorption amount of Pb(II) by different materials, and the right column (red) represents the equilibrium adsorption amount of Cd(II) by different materials. Figure 1 As shown, the results showed that *P-mZVIBC 500 The absorption capacity for Pb(II) and Cd(II) is the lowest. This low adsorption capacity is due to the limitations of non-ball-milled composites due to agglomeration, low reactivity and poor component integration. The removal capacity of ball-milled mZVI for Pb(II) and Cd(II) is very limited. P-mZVI has significantly improved Pb(II) and Cd(II) compared with mZVI. This is because the addition of phosphate prevents the oxidation of mZVI, increases the reaction sites on the surface of P-mZVI, enhances the stability of mZVI, and strengthens the removal mechanism, thereby improving the overall removal efficiency. In addition, compared with P-mZVI, P-mZVIBC 500 The removal of Pb(II) and Cd(II) increased significantly, which was due to the increase in biochar, which promoted the dispersion of mZVI particles and provided more reaction sites for pollutant adsorption and chemical reactions. Therefore, P-mZVIBC was finally selected. 500 As a remediator for lead and cadmium co-contaminated soil.

[0061] 2. Characterization (SEM, IR and X-ray diffraction):

[0062] P-mZVIBC was characterized by scanning electron microscopy (model: Gemini300), infrared spectrometer (model: Bruker Tensor II), and X-ray diffraction system (model: USAK-Alpha1063). 500 Morphological observation and structural characteristics analysis of I.

[0063] Figure 2 Indicates P-mZVIBC in Example 1 500 SEM images of Figure 2 As shown, mZVI particles exist stably in biochar, preventing the agglomeration of mZVI, and phosphate is evenly distributed on the surface of mZVI and biochar to form a coating, further reducing the agglomeration of mZVI.

[0064] Figure 3 Indicates P-mZVIBC in Example 1 500 and infrared spectra of P-mZVI; Figure 3 As shown, at 918cm -1 、1098cm -1 and 530cm -1 The stretching vibrations of CP and PO bonds were observed at 1300 cm -1The peak at is the characteristic of the P=O bond, which further confirms the existence of the phosphate group. It is inferred that a phospho-iron compound is formed on the surface of mZVI to replace the original iron oxide, thereby slowing down the oxidation process of mZVI under normal conditions.

[0065] Figure 4 Indicates P-mZVIBC in Example 1 500 and X-ray diffraction patterns of P-mZVI; Figure 4 As shown in Figure 2, 44.38°(110) is the characteristic peak of mZVI, and this peak appears in both composites, indicating that the core mZVI structure remains intact. 500 The peak at 23.64°(012) indicates the formation of iron phosphate compounds, further proving that ball milling can incorporate phosphate species into the surface of the material.

[0066] 3. Effect of pH:

[0067] The adsorption process is: use a balance to weigh 0.05±0.005g of the repair agent P-mZVIBC 500 , add it to a 150mL conical flask, then add 100mL of 100mg / L Pb(II) and Cd(II) solution to the conical flask, adjust the initial pH value of the solution with 0.1mol / LNaOH or HCl, and set the pH range to 2.0-7.0, respectively. After shaking at 200rpm for 4h at 25℃, the concentrations of Pb(II) and Cd(II) in the solution were measured, and the removal rate of the adsorption material was calculated.

[0068] Figure 5 Indicates P-mZVIBC in Example 1 500 The removal effect of Pb(II) and Cd(II) at different pH values, the upper curve represents the removal effect of Pb(II), and the lower curve represents the removal effect of Cd(II); Figure 5 As shown, P-mZVIBC 500 The removal capacity of Pb(II) and Cd(II) increased significantly with the increase of pH from 2 to 5. However, between 5 and 7, the removal capacity of Pb(II) and Cd(II) increased only slightly. This is due to the 500 The pH value of zero charge is 3.71. When the pH value is lower than 3.71, there are many H + ions, making P-mZVIBC 500 The positively charged functional groups on P-mZVI-BC are protonated, which creates repulsive forces with Pb(II) and Cd(II), hindering their adsorption. 500The surface of P-mZVIBC is negatively charged, which increases its affinity with Pb(II) and Cd(II), thereby increasing their removal efficiency. 500 The removal efficiency of pollutants can reach a high level in a wide pH range, indicating that it has good tolerance to pH.

[0069] 4. The influence of time:

[0070] The adsorption process is: use a balance to weigh 0.05±0.005g of the repair agent P-mZVIBC 500 , add it to a 150mL conical flask, then add 100mL of 100mg / L Pb(II) and Cd(II) solution to the conical flask, shake at 200rpm for 4h at 25℃, measure the concentrations of Pb(II) and Cd(II) in the solution during 5min, 20min, 40min, 60min, 90min and 240min, and calculate the removal rate of the adsorption material.

[0071] Figure 6 Indicates P-mZVIBC in Example 1 500 The removal effect of Pb(II) and Cd(II) at different times, the upper curve represents the removal effect of Pb(II), and the lower curve represents the removal effect of Cd(II); Figure 6 As shown in Figure 2, the removal rates of Pb(II) and Cd(II) increased rapidly in the first 20 min and 10 min, respectively, indicating that the ball-milled composites had a large number of adsorption sites for Pb(II) and Cd(II) to bind; equilibrium was reached around 60 min, which means that P-mZVIBC 500 The adsorption sites on the surface of the nanostructured carbon nanotubes are gradually fully occupied. The Avrami kinetic model best describes the binding of Pb(II) and Cd(II), indicating the existence of multiple kinetics between Pb(II) and Cd(II) and the composites during the adsorption process. The intraparticle diffusion model shows that the adsorption process is divided into two stages: the initial external surface binding stage, followed by intraparticle diffusion.

[0072] 5. Influence of temperature:

[0073] The adsorption process is: use a balance to weigh 0.05±0.005g of the repair agent P-mZVIBC 500 , add it to a 150mL conical flask, then add 100mL of 50-200mg / L Pb(II) or 10-50mg / L Cd(II) solution to the conical flask, shake at 200rpm for 4h at 25℃, 35℃ and 45℃, measure the concentrations of Pb(II) and Cd(II) in the solution, and calculate the removal rate of the adsorbent material.

[0074] Figure 7 Indicates P-mZVIBC in Example 1 500 The removal effect of Pb(II) at different temperatures, the curves from top to bottom are 45℃, 35℃ and 25℃, Figure 8 Indicates P-mZVIBC in Example 1 500 The removal effect of Cd(II) at different temperatures, the curves from top to bottom are 45℃, 35℃ and 25℃. Figure 7-8 As shown in the figure, at different temperatures, as the initial content increases, the removal of Pb(II) and Cd(II) also gradually increases due to the increase in active sites. As the pollutant concentration further increases, fierce competition occurs between the limited activation sites, resulting in a relatively slow increase in the adsorption of Pb(II) and Cd(II) until the adsorption equilibrium is reached. In addition, the adsorption of Pb(II) and Cd(II) decreases with increasing temperature, indicating that the process is exothermic.

[0075] 6. Soil experiment:

[0076] Experimental conditions: Soil samples were collected, dried under ambient conditions, and then treated with a contaminated solution containing 2.5 mg / kg Cd(II) and 500 mg / kg Pb(II) and screened with a 20-mesh sieve. The soil was then incubated at 40% humidity for 20 days. Different materials were used to fix Cd(II) and Pb(II). During the entire remediation process, 1% of different types of adsorbents (mZVI, P-mZVI, and P-mZVIBC) were applied to the soil at a moisture content of 40% and a pH of 6.2±0.5. 500 ) was conducted for 20 days of remediation experiment, and samples were collected at intervals of 0, 1, 5, 10, 15 and 20 days. The concentrations of available cadmium (A-Cd) and available lead (A-Pb) in the soil were determined by DTPA extraction method.

[0077] Fig. 9 The figure shows the repair effect of different repair agents on Pb (II) and Cd (II) in soil in Example 1. The left column shows the equilibrium adsorption amount of Pb (II) by different materials, and the right column shows the equilibrium adsorption amount of Cd (II) by different materials; Fig. 9 As shown, after 20 days of treatment, the levels of A-Cd and A-Pb were significantly reduced. Compared with the control (CK), mZVI, P-mZVI and P-mZVIBC 500The A-Cd in the treated soil was reduced from 1.64 mg / kg to 1.14 mg / kg, 0.63 mg / kg and 0.26 mg / kg respectively; the A-Pb was reduced from 26.23 mg / kg to 14.80 mg / kg, 8.78 mg / kg and 4.58 mg / kg respectively. 500 The soil A-Cd and A-Pb were reduced by 30.49% and 43.58% respectively. This is because the individual iron particles tend to agglomerate after entering the soil, and due to their easy oxidation characteristics, an inert oxide shell is formed on the surface, which inhibits the removal performance of soil A-Cd and A-Pb; P-mZVIBC 500 The soil A-Cd and A-Pb were reduced by 84.20% and 82.52% respectively, achieving a good removal effect. This may be because biochar has a strong dispersing effect on the composite material, inhibiting the agglomeration of the material after entering the soil. Phosphate will form a phosphorylated oxidation shell on the surface of the composite material, further weakening the agglomeration phenomenon and effectively preventing the oxidation of the material, which is beneficial to the reaction process between the composite material and the pollutants in the soil. In summary, P-mZVIBC 500 It is a highly effective soil heavy metal passivator.

Claims

1. A method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar, characterized in that The preparation method is carried out according to the following steps: Step S1: preparing biochar; The pretreated banana peel powder is placed in a tube furnace, heated to 400-600° C. in a nitrogen atmosphere, and pyrolyzed at 400-600° C. for 110-130 minutes; after the pyrolysis, the banana peel powder is soaked in a hydrochloric acid solution, and then rinsed and dehydrated to obtain biochar; Step S2: preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar; The biochar obtained in step S1 is placed in a ball mill with micron zero-valent iron and KH2PO4, wherein the grinding balls in the ball mill are composed of large balls, medium balls and small balls, and the number ratio of the large balls, medium balls and small balls is (1-3): (15-17): (14-16); the ball mill is placed in a planetary ball mill, and after ball milling for 6-18 hours, it is sieved through a 100-mesh sieve to obtain a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar.

2. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that The pretreated banana peel powder described in step S1 is processed according to the following steps: the banana peel is rinsed with distilled water and then dried in an oven at 70 to 90° C. for 12 to 36 hours; after drying, the banana peel is ground and then sieved with a 100-mesh sieve to obtain banana peel powder with a particle size of 0.13 to 0.17 mm.

3. The method for preparing a composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that The nitrogen introduction rate in step S1 is 140-160 mL / min.

4. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that In step S1, the temperature is increased to 400-600°C at a heating rate of 5-10°C / min.

5. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that In step S1, the banana peel powder is placed in a 0.05-0.15M hydrochloric acid solution and soaked for 10-12 hours.

6. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that In step S1, dehydration is performed at 70 to 90°C.

7. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that The rotation speed of the ball mill in step S2 is 200-400 rpm.

8. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1 or 7, characterized in that In step S2, the rotation direction of the ball milling process is reversed every 2 to 4 hours.

9. The method for preparing a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar according to claim 1, characterized in that The mass ratio of the biochar, micronized zero-valent iron and KH2PO4 described in step S2 is (0.1-0.2): (0.4-0.6): (0.7-0.8).

10. Application of a composite functional material of ball-milled micronized zero-valent iron doped with phosphate and biochar prepared by the method according to any one of claims 1 to 9, characterized in that The composite functional material of ball-milled micron zero-valent iron doped with phosphate and biochar is used to remove chromium from water and soil.

Citation Information

Patent Citations

  • Preparation method and application of carbon-sulfur doped zero-valent iron composite material

    CN110482671A

  • Micron zero-valent iron-loaded biochar for removing hexavalent chromium, and preparation method and application thereof

    CN113173608A

  • Ball-milled zero-valent iron doped sulfur / biochar composite material as well as preparation method and application thereof

    CN114789040A

  • Ball-milling modified charcoal loaded zero-valent iron composite material as well as preparation method and application thereof

    CN114797746A

  • Phosphorus-doped zero-valent iron modified material, preparation method thereof and method for efficiently reducing and removing pollutants by using phosphorus-doped zero-valent iron modified material

    CN115784412A